New technology in water services proceedings of a symposium organized by the Institution of Civil Engineers and held in London on 20-21 February 1985. (Thomas Telford, 1985)
The focus of these papers is new technology in water services. Hardware and modern communications techniques are discussed, as well as managerial and practical requirements from the user's viewpoint.